From amputation to reintegration - Prešern-Štrukelj, Metka (Rehabilitacija (Ljubljana), 2008)
The article discusses the program of rehabilitation and reintegration of patients with low-limb amputation, who had undergone amputation at the Medical Clinical Center Maribor and were then, in regard to their functional state, referred to rehabilitation at the Institute for Rehabilitation, Republic of Slovenia. We retrospectively followed 58 patients. In our research 88 % of included patients were fitted with prostheses and were able to walk acceptable distance. The functional state of the patients at discharge was based on gait tests and the improved assessment of motor abilities on the Functional Independence Measure (FIM). The follow up of amputee patients is important part of complete rehabilitation program. Their reintegration has to be followed and carefully stimulated by rehabilitation team.
Keywords: Amputacija; Amputation; Lower Extremity; noga; Rehabilitacija; Rehabilitation; Spodnja okončina